Research Productivity in Business and Economics: South Korea, 1990-2016 - Jang C. Jin (East Asian Economic Review (EAER), 2019)
This paper ranks higher education in Korea based upon research productivity in business and economics disciplines. The number of SCI-level journal articles are tabulated using the Web of Science search engine, over the sample period from 1990 to 2016. The league table shows that many private universities dominate top-tier ranks, which is consistent with the school reputations most commonly cited by the general public in Korea. In contrast, many national universities appear in the second-tier, and their scanty performance in business and economics is in sharp contrast with our earlier findings in which national universities performed well in science and engineering fields (Jin and Kim, 2018). In addition, the ranking order in lower-ranked schools is found to be sensitive to a small change in publications, whereas the publication gap among top-tier schools is relatively large. Finally, unlike our general perception, the size of school does not matter for collaborative research. Some policy implications are discussed as a conclusion.
Keywords: A10; A14; A20; 330; Research Productivity; SCI-level Journal Publications; Higher Education; University Ranking; School Competitiveness